Programme Evaluation Review Technique - a New Approach to Logging Management - Misra, S. K.; Dutta, A. K.; Bagdwal, V. S. (Indian Forester, 1981)
"Programme Evaluation Review Technique" is one of the latest modern technique for the planning, scheduling and controling of complex projects. There is a great scope of using this technique in Forestry Projects. Timber harvesting, includes, a large number of interdependent operations, which are like links of a chain. With the departmentalisation of forest working, logging has become more complicated in recent years. An attempt has been made in this article on the appliciltion of this tool on a simulated timber harvesting project. The project under consideration consist of 59 interdependent activities and the total time of the project is 305 days. The main thrust of this technique i.e. Net work has been drawn to find out the critical path of this project. It is observed that out of 59 activities only 16 activities, are critical. Forest manager should pay maximum attention to this critical activities, to control the progress and to finish the project in target time of 305 days.